Cohort Profile: The Hunter Community Study - McEvoy, M.; Smith, W.; D'Este, C.; Duke, Janine; Peel, R.; Schofield, P.; Scott, R.; Byles, J.; Henry, D.; Ewald, B.; Hancock, S.; Smith, D.; et al. (Oxford University Press, 2010)
In almost every country, the proportion of people aged >60 years is growing faster than any other age group and is expected to reach 2 billion worldwide by 2050.1 Internationally and nationally, considerable efforts are being made to promote active ageing.2–4 However, Australia lacks the kind of comprehensive longitudinal research underway in Europe and North America.5,6 Although Australia does have a number of longitudinal studies designed to address various issues of health and ageing among older adults,7,8 only a few of these studies include a broad and comprehensive range of physical and biological measures. The Hunter Community Study (HCS) is a collaborative study between the University of Newcastle’s School of Medicine and Public Health and the Hunter New England Area Health Service. It is a multi-disciplinary initiative that was established to fill some existing gaps in ageing research in Australia and is unique in that it has collected detailed information across all six key policy themes as identified in the Framework for an Australian Ageing Research Agenda.